PENGARUH HARGA DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ONLINE SHOP TOKOPEDIA.COM DI FAKULTAS EKONOMI JURUSAN MANAJEMEN UNIVERSITAS NEGERI MEDAN - Dita Amanah; Adinda Ayu Layla (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara)
This study aims to determine the effect of price and completeness of products on consumer purchasing decisions online shop Tokopedia.com at Faculty of Economics Department of Management State University of Medan. The sample in this study were all students of the Faculty of Economics Department of Management University of Medan which is still active and shopping in Tokopedia.com as many as 122 respondents. The test used is the test data quality and classical assumption. The hypothesis test uses multiple linear regression analysis, F test and t test. Validity of test results obtained radding> rtable for each item reliability test questions and questionnaires obtained a Cronbach alpha of each variable is 0.805 for the variable X1, 0.759 for variable X2 and 0.794 for the variable Y. This value is greater than the level that is significantly rtable 0.361. The data analysis of each variable regression equation Y = 8.986 + 0.143 x1 + 0.178 x2 + e. Retrieved R2 of 0.487, which is means the X1 and X2 explain the effect on variable Y of 48.7% while the remaining 51.3% described variables out of the company. The resulting partial test each independent variables affect the dependent variable with research significance less than 0.05, and the results of the test-simultaneous calculation of 4.156 with Ftable 3.07, which is means Fadding > F table with a level of significant (α) 0,000 <0, 05, which is means that the hypothesis is accepted that price and completeness of the product together significantly influence on consumer purchase decisions online shop Tokopedia.com at Faculty of Economics Department of Management State University of Medan.